Calcium-Mediated Dual-Mode Regulation of Cardiac Sodium Channel Gating - Biswas, Subrata (2009)
Intracellular Ca(2+) ([Ca(2+)](i)) can trigger dual-mode regulation of the voltage gated cardiac sodium channel (Na(V)1.5). The channel components of the Ca(2+) regulatory system are the calmodulin (CaM)-binding IQ motif and the Ca(2+) sensing EF hand–like (EFL) motif in the carboxyl terminus of the channel. Mutations in either motif have been associated with arrhythmogenic changes in expressed Na(V)1.5 currents. Increases in [Ca(2+)](i) shift the steady-state inactivation of Na(V)1.5 in the depolarizing direction and slow entry into inactivated states. Mutation of the EFL (Na(V)1.5(4X)) shifts inactivation in the hyperpolarizing direction compared with the wild-type channel and eliminates the Ca(2+) sensitivity of inactivation gating. Modulation of the steady-state availability of Na(V)1.5 by [Ca(2+)](i) is more pronounced after the truncation of the carboxyl terminus proximal to the IQ motif (Na(V)1.5(Δ1885)), which retains the EFL. Mutating the EFL (Na(V)1.5(4X)) unmasks CaM-mediated regulation of the kinetics and voltage dependence of inactivation. This latent CaM modulation of inactivation is eliminated by mutation of the IQ motif (Na(V)1.5(4X-IQ/AA)). The LQT3 EFL mutant channel Na(V)1.5(D1790G) exhibits Ca(2+) insensitivity and unmasking of CaM regulation of inactivation gating. The enhanced effect of CaM on Na(V)1.5(4X) gating is associated with significantly greater fluorescence resonance energy transfer between enhanced cyan fluorescent protein–CaM and Na(V)1.5(4X) channels than is observed with wild-type Na(V)1.5. Unlike other isoforms of the Na channel, the IQ-CaM interaction in the carboxyl terminus of Na(V)1.5 is latent under physiological conditions but may become manifest in the presence of disease causing mutations in the CT of Na(V)1.5 (particularly in the EFL), contributing to the production of potentially lethal ventricular arrhythmias.